Prática e teoria no desenvolvimento: Questão da tomada de consciência - Montoya, Adrián Oscar Dongo [UNESP] (My University, 2017)
The psychological study of moral development, as well as of affective and intellectual life, highlights the need to establish relationships between the child's practical action and reflection on his or her own actions and those of other individuals. However, analyzing these relationships requires taking into account the process that may make them intelligible: awareness. In this work, we will analyze these questions from some basic questions that refer to moral development: How does the child think the moral rules in the practice of the acts themselves and outside of them? Is there a correspondence between the moral judgments and the moral practice of the child? In the formation of heteronomous morality and autonomous morality, are moral practices and judgments the same? Do judgments result from the awareness of moral practices? In this study, we will highlight these problems and point out ways of solution that are shown in the psychogenetic research of Jean Piaget.
Practice and theory in the moral development: Question of awareness
Keywords: Cognition; Moral development; Relation between theory and practice